2013
DOI: 10.1186/1477-7525-11-25
|View full text |Cite
|
Sign up to set email alerts
|

Impact of malocclusion on oral health related quality of life in young people

Abstract: BackgroundThe objectives for this study were to assess Oral Health Related Quality of Life (OHRQoL) in young people aged 15–25 who sought orthodontic treatment, and to measure the association between orthodontic treatment need (using the IOTN), sex, age and education level, and oral health related quality of life (OHRQoL).MethodsSurvey of a consecutive series of 323 young adults aged 15 to 25 years, attending orthodontic clinics at the Faculty of Dentistry, Universiti Teknologi MARA. Participants completed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
123
4
17

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(158 citation statements)
references
References 28 publications
14
123
4
17
Order By: Relevance
“…Similar results were observed in a study that evaluated the relationship between enamel defects and quality of life in schoolchildren between 11 and 14 years of age 24 . This result was also observed in individuals with caries, malocclusions, and temporomandibular disorders [25][26][27] . However, these data were not collected in this study, constituting a limitation of this research, because these factors can be confounding variables.…”
Section: Discussionsupporting
confidence: 62%
“…Similar results were observed in a study that evaluated the relationship between enamel defects and quality of life in schoolchildren between 11 and 14 years of age 24 . This result was also observed in individuals with caries, malocclusions, and temporomandibular disorders [25][26][27] . However, these data were not collected in this study, constituting a limitation of this research, because these factors can be confounding variables.…”
Section: Discussionsupporting
confidence: 62%
“…This has been found in non-clinical populations (mainly schoolchildren) [65][66][67][68][69][70][71][72][73][74] as well as young people referred for orthodontic treatment. 11,[75][76][77][78][79][80][81][82][83][84][85] The principal areas that impacts are registered are in the questionnaire domains that record emotional and social well-being. A systematic review of the literature concluded that the relationship between malocclusion/orthodontic treatment need and OHQoL was moderate; 86 however due to differences in methodologies between studies, the authors commented that they were unable to undertake a meta-analysis to investigate the statistical relationships more fully.…”
Section: Quality Of Lifementioning
confidence: 99%
“…En otro estudio, el dominio malestar fue el que registró mayor impacto, así como también estuvo afectado en el grupo 15-18 años de edad que mostró el mayor impacto en su calidad de vida debido a la maloclusión. Los participantes con una formación universitaria reportaron un impacto significativamente mayor en comparación con los participantes con una educación secundaria (Masood et al, 2013).…”
Section: Introduccionunclassified